Zwitterionic 3D-Printed Non-Immunogenic Stealth Microrobots - Cabanach, Pol (Adv Mater, 2020)
Microrobots offer transformative solutions for non-invasive medical interventions due to their small size and untethered operation inside the human body. However, they must face the immune system as a natural protection mechanism against foreign threats. Here, non-immunogenic stealth zwitterionic microrobots that avoid recognition from immune cells are introduced. Fully zwitterionic photoresists are developed for two-photon polymerization 3D microprinting of hydrogel microrobots with ample functionalization: tunable mechanical properties, anti-biofouling and non-immunogenic properties, functionalization for magnetic actuation, encapsulation of biomolecules, and surface functionalization for drug delivery. Stealth microrobots avoid detection by macrophage cells of the innate immune system after exhaustive inspection (>90 hours), which has not been achieved in any microrobotic platform to date. These versatile zwitterionic materials eliminate a major roadblock in the development of biocompatible microrobots, and will serve as a toolbox of non-immunogenic materials for medical microrobot and other device technologies for bioengineering and biomedical applications.